Assessing pharmaceutical consultations: Comparing pharmacy-recommended medications for minor ailments and regulatory compliance in a Latin American healthcare network - Esteban Zavaleta-Monestel; Jorge Arturo Villalobos-Madriz; Bruno Serrano-Arias; Sebastián Arguedas-Chacón; José Pablo Diaz-Madriz; Mery Alejandra Ferreto-Meza; Betzy María Romero-Chavarría; Priscila Zumbado-Amerling (Exploratory Research in Clinical and Social Pharmacy, 2023)
Background: The importance of access to medicines in promoting global health cannot be overstated, particularly as an estimated 2 billion people lack access to basic medicines, particularly in developing nations. While over-the-counter (OTC) medications are relatively safe and cost-effective, there is a risk of misuse due to factors such as inaccurate self-diagnosis, inadequate dosing, addiction, adverse drug reactions, and drug interactions. To ensure proper use and prevent irrational self-medication, pharmacists can play a crucial role in guiding patients. However, the legislation in Costa Rica only covers OTC and prescription drugs, and health authorities are proposing a new decree to include a list of drugs that can be recommended by pharmacists without a prescription to treat minor ailments, which would be classified as behind-the-counter (BTC). Objective: Characterize the pharmaceutical consultation, compare the medications recommended by pharmacy professionals for minor ailments with the legislation in force in Costa Rica, and determine whether the current OTC medications are sufficient to treat minor ailments. Material and methods: This study is a descriptive, observational, cross-sectional study that focuses on a sample of the Costa Rican population that comes to consult with a pharmacist in one of the four pharmacies of the Hospital Clínica Bíblica (HCB) in San José, Costa Rica. Consultations included users over 18 years of age or caregivers of underage patients seeking advice or assistance from publicly accessible pharmacies, excluding consultations that involved information related to other hospital departments. This study aims to analyze the pharmaceutical consultation for minor ailments and compare the medications recommended by pharmacists with the list of medications allowed in Costa Rica. The study also aims to determine if the current OTC medications are adequate for treating minor ailments. Results: A total of 1537 consultations were gathered, which were divided into four categories: pharmaceutical recommendation (48%), medication information (31%), other consultations (18%), and referrals to another health professional (3%). Among the consultations classified as pharmaceutical recommendations, 90% were related to minor ailments. Prescription drugs accounted for 75.3% of the medications recommended and consulted. However, when the BTC category was included, the percentage of recommended prescription drugs decreased to 29.6%, while BTC drugs constituted 45.7%. Finally, the chi-square test rejected the null hypothesis that there was no association between the availability of OTC drugs and the minor ailments for which patients sought consultation. Conclusions: Most cases of pharmacy consultations involve minor illnesses such as digestive symptoms, joint pain, and respiratory issues. The proposed decree by health authorities in Costa Rica is noteworthy as it establishes standardized protocols for the prescription of BTC medications to ensure the safety of patients.